Measuring Socioeconomic Health Inequalities in Presence of Multiple Categorical Information - Makdissi, Paul; Yazbeck, Myra (Université d'Ottawa | University of Ottawa, 2012)
While many of the measurement approaches in health inequality measurement assume the existence of a ratio-scale variable, most of the health information available in population surveys is given in the form of categorical variables. Therefore, the well-known inequality indices may not always be readily applicable to measure health inequality as it may result in the arbitrariness of the health concentration index's value. In this paper, we address this problem by changing the dimension in which the categorical information is used. We therefore exploit the breadth of this information, define a new ratio-scaled health status variable and develop positional stochastic dominance conditions that can be implemented in a context of categorical variables. We also propose a parametric class of population health and socioeconomic health inequality indices. Finally we provide a twofold empirical illustration using the Joint Canada/United States Surveys of Health 2004 and the National Health Interview Survey 2010. / Bien que plusieurs approches à la mesure des inégalités de santé font comme hypothèse qu’il existe une variable d’échelle de ratio, l’information que l’on retrouve dans les enquêtes sur la santé de la population prend souvent la forme de variables catégoriques. Dans ce contexte, les indices d’inégalité connus peuvent ne pas être directement applicables à la mesure des inégalités de santé puisqu’ils produiront des valeurs arbitraires. Dans cet article, nous apportons une solution à ce problème en changeant la dimension dans laquelle l’information catégorique est utilisée. Nous exploitons l’étendue de cette information afin de définir une nouvelle variable d’échelle de ratio et nous développons des tests de dominance stochastique qui peuvent être ainsi implémentés dans le contexte de variables catégoriques. Nous proposons aussi une classe paramétrique d’indices de santé de la population et d’indices d’inégalité socioéconomique de santé. Finalement, nous proposons deux illustrations basées sur l’Enquête conjointe Canada/États-Unis sur la santé et le National Health Interview Survey 2010.
Keywords: Population Health; Health Inequality; Stochastic Dominance; Santé de la population; inégalité de santé; dominance stochastique